(3GdQSGdI GdMqLJjIs - (3bGSe Hf eMehO GdbjUQis ((3CMeO Hf Ndjd GdJhbGOi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi jOd Ydjg GdBjGJ GdcHQi ajbhd GdbjUQi deG GdMfj ef dG jSYfi eNGdaJg s
(3Vef eLehY s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeYGQa GdYGeIs